Association between sarcopenia and falls in Chinese older adults: Findings from the China health and retirement longitudinal study. - Chunhua Yang; Tengfei Ye; Yan Gao (PLoS ONE)
Falling has become a significant factor in the mortality of elderly people. Little is known about whether sarcopenia can be a risk factor for falls in older adults. This study aims to assess the association between sarcopenia and falls among older Chinese according to the updated diagnostic guidelines of the Asian Working Group on Sarcopenia 2019 (AWGS 2019). We used data from the 2011 baseline and 2015 follow-up survey of the China Health and Retirement Longitudinal Study (CHARLS). This study examined the relationship between sarcopenia status and falls through cross-sectional analysis. Cox proportional hazards regression models were conducted to investigate the effect of sarcopenia status on subsequent falls, with the report of hazard ratio (HR). A total of 5,337 participants aged at least 60 years (51.3% men; mean age 67.6 ± 6.3) were enrolled in this analysis from the CHARLS 2011. The study revealed that the prevalence of falls was significantly higher in the possible sarcopenia and sarcopenia groups compared to the no sarcopenia group, with rates of 15.8%, 19.4%, and 24%, respectively. Logistic regression was utilized to investigate the association between sarcopenia and falls. Both possible sarcopenia (OR: 1.22, 95% CI: 1.03-1.45) and sarcopenia (OR: 1.64, 95% CI: 1.23-2.19) were positively associated with higher odds of falls (all p < 0.05). During the 4 years of follow-up, 1490 cases (29.9%) with incident falls were identified. In the longitudinal analysis, individuals with diagnosed sarcopenia (HR: 1.32, 95% CI: 1.11-1.57) were more likely to have new-onset incident falls than their no-sarcopenia peers. Sarcopenia in the elderly is an independent risk factor for falls, with health screening and intervention reducing fall risk and improving quality of life.